2014
DOI: 10.1177/0004563214533317
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BD Vacutainer® Rapid Serum Tube and plasma for haemolysis markers in the emergency department

Abstract: Background: In recent years, a rapid-clotting serum tube, BD Vacutainer Õ Rapid Serum Tube (RST TM ), was introduced to improve turn-around times for serum samples. Previous studies reported reduced concentrations of some markers of haemolysis in RST specimens compared to other serum or plasma samples. We aimed to compare RST to plasma tubes for haemolysis markers in an emergency department (ED) setting, where increased rates of haemolysis are commonly seen. Methods: Patients presenting to ED over an eight-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Several studies evaluated factors attributed to the hemolysis of blood samples particularly from ED. Causes and nature of hemolytic specimen are multiple [5] but the collection techniques in the ED appeared to be the origin of the increased hemolysis rate problem [12,13]. Recently, Phelan study confirmed previous findings that straight stick and antecubital location are significantly associated with reduced hemolysis and indicated that shorter tourniquet time and larger gauge for IV draws were significantly associated with lower hemolysis [14].…”
Section: Discussionmentioning
confidence: 93%
“…Several studies evaluated factors attributed to the hemolysis of blood samples particularly from ED. Causes and nature of hemolytic specimen are multiple [5] but the collection techniques in the ED appeared to be the origin of the increased hemolysis rate problem [12,13]. Recently, Phelan study confirmed previous findings that straight stick and antecubital location are significantly associated with reduced hemolysis and indicated that shorter tourniquet time and larger gauge for IV draws were significantly associated with lower hemolysis [14].…”
Section: Discussionmentioning
confidence: 93%
“…Fast clot activation results in the more rapid separation of blood cells from serum. 2 Although serum glucose concentrations tend to be high in quick-clotting tubes than SSTs, 10,12,18 it is measured at a lower concentration than in lithium heparin tube and gold standard. 19 In addition, blood collection tubes containing clot activator and lithium heparin are not suitable for glucose measurement; 9,20 the use of VQ-tube alone should be avoided in order to accurately measure glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported studies suggested that shortened clotting time contributed bias to serum glucose as well as LD concentration between the tubes. 2,21 Differences in concentrations of LD are frequently reported 1012,18 in rapid clotting serum tubes compared with general SSTs. Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the comparison statistics, results below the assay limit of detection (1.9 ng/L) were assigned that value. Details of the sample collection can be found in [6].…”
mentioning
confidence: 99%